Development of Ca(OH)2nanosorbent for intermediate-high temperature CO2 capture via wet chemical route in N,N-Dimethylformamide solvent - Mohd Daud, Farah Diana; Sreekantan, Srimala; Mohamed, Abdul Rahman (Trans Tech Publications Ltd., 2014)

(untitled)
CO2 is the major anthropogenic greenhouse gas which contributes to the increasing atmospheric CO2 concentration, leading to serious global warming and climate change. Thus, the present paper investigates the CO2-capture performance of synthesized calcium hydroxides, Ca(OH)2nanosorbent at intermediate-high temperatures which are 350, 450, 550 and 650ºC. CO2 adsorption performance was analysed by thermo-gravimetric analyser (TGA).The CO2 adsorption temperature strongly influenced the capture performance of the sorbent. Facile wet chemical technique was utilized to synthesize Ca(OH)2 nanorod sorbent structures using calcium nitrate tetrahydrate, Ca(NO3)2.4H2O as the calcium precursor, and precipitated with sodium hydroxides (NaOH) in N,N-Dimethylformamide (DMF) mixed deionized(DI) water media at 55 ºC. X-ray diffraction (XRD) result exhibited Ca(OH)2hexagonal crystal structures. The Ca(OH)2 particle size and morphological properties before and after CO2 adsorption are studied by Field Emission Scanning Electron Microscopy(FESEM). The FESEM image indeed showed the rod like shape of Ca(OH)2nanosorbent with rod length approximately700 nm while the diameter 140nm. When CO2 molecules were adsorbed by Ca(OH)2nanosorbent, the nanorod structures are changed to rigid interconnected each other like a lump shaped. Ca(OH)2nanosorbentseems to be a potentially good absorbent for capturing CO2when increased temperatures. However, at intermediate temperature 350 and 450ºC, the synthesized Ca(OH)2nanosorbent demonstrated higher CO2 adsorption (141 to 220 mg/g CO2)than others intermediate temperature CO2 sorbent such as layer double hydroxides(LDH), lithium zirconates (LiZrO3) and hydrotalcite.